Aplikasi Sensor Gesture Untuk Kendali Lampu Dengan NODEMCU ESP8266 - Tony Wungkana; Sukandar Sawidin; Nikita Sajangbati; Toban T Pairunan; Benny A.P Loegimin (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2022)
To turn on the indoor lighting is still done manually by pressing the light switch. Switch is an electric tool to turn on or turn off the lights. There are lots of innovations that can be done to make human work easier. One of them is using a gesture.sensor which is applied to replace a manual switch. Gesture.sensor is a non-verbal communication that communicates certain messages by detecting hand movements. This research is to utilize the gesture sensor which functions as a control for disconnecting and connecting electricity without physical contact between the user and the device being made, to turn on the lights in the room, the gesture sensor detects hand movements up, down, to the left and to the right side. If there is a movement of the hand as a gesture signal (gesture.sensor) as input and processed by the NodeMCU ESP8266 microcontroller which is used as input to the relay module to turn on or turn off the lights